ENHANCING STUDENTS' READING COMPREHENSION ABILITY ON NARRATIVE TEXT THROUGH STORYTELLING AND JIGSAW TECHNIQUE - Hafifah, Nuzul; Wiranegara, Dian Arsitades (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Reading comprehension ability is the foundation of students in mastering the various abilities and knowledge of English needed by students. Having good reading comprehension ability skills helps students in understanding the meaning of the reading contained in a reading. In this study, the researcher conducted a study that aimed to analyze and enhance students' reading comprehension ability of narrative texts when storytelling and jigsaw techniques were applied and students' perceptions when these two things were applied. Here, the researcher applied a case study research design using a qualitative descriptive analysis method in which the researcher described and analyzed how students' reading comprehension ability of narrative texts when storytelling and jigsaw techniques are applied, as well as students' perspectives on it. For data collection, researchers used observation and interviews as research instruments. The results showed that when the teacher applied storytelling and jigsaw techniques in learning reading comprehension ability of narrative texts, students’ reading comprehension ability of narrative texts were enhanced. Students can understand the general structure and elements of narrative text well. In addition, students can also identify the main ideas, factual information, references, and inferences contained in the text that has been presented by the teacher. The application of these two things in learning reading comprehension ability of narrative texts also gets a positive perspective from students. The students explained that they liked group discussions regarding the narrative text material given to them by the teacher and the storytelling activities carried out by their group mates.